Penerapan TGT Menggunakan Educaplay dalam Upaya Meningkatakan Hasil Belajar Bahasa Indonesia Pada Siswa Kelas VI SD - Aprillia, Deonety; Bahtiar, Reza Syehma; Santoso, Edi (Journal of Science and Education Research, 2025)
This study consists of four stages, namely 1) action planning such as preparing all the instruments needed in the study, 2) implementing the Teams Games Tournament (TGT) learning model, 3) observation and evaluation, and 4) reflection carried out in each cycle. The application is the Team Game Tournament model by utilizing the Educaplay platform. Activating students and helping them specifically discuss the Application of the Teams Game Tournament type cooperative learning model to solve questions individually. The research method used is classroom action research (CAR). Classroom action research is a form of structured scientific study, with implementations that can be observed, felt, and experienced by using various actions to improve the learning process and outcomes (Ramadhan, 2022). This research was conducted in semester I. The determination of the research time refers to the academic calendar VI of SDN Dukuh Kupang 1. The subjects of this study were grade IV students consisting of 12 female students and 15 male students. The object of this study is the learning motivation and speaking skills of students in the Indonesian language subject through the application of the Teams Games Tournament learning model. The research data shows that the percentage of learning outcome completion continues to increase from pre-cycle, cycle I, to cycle II. This can be seen from the results of data analysis, where the student completion value at the pre-cycle stage is 57%, in cycle I is 71%, and in cycle II reaches 94%. In cycle II, students are already actively involved in learning.